Respuestas
Respuesta dada por:
2
2x - 5y = - 14 (3)
3x + 4y = 2 (-2)
___________
6x - 15y = - 42
-6x - 8y = - 4
___________
0 - 23y = - 46
___________
y = - 46/-23
y = 2
Reemplazando en 3x+4y=2
3x+4(2)=2
3x+8=2
3x= - 6
X= - 6/3
X= - 2
3x + 4y = 2 (-2)
___________
6x - 15y = - 42
-6x - 8y = - 4
___________
0 - 23y = - 46
___________
y = - 46/-23
y = 2
Reemplazando en 3x+4y=2
3x+4(2)=2
3x+8=2
3x= - 6
X= - 6/3
X= - 2
Preguntas similares
hace 6 años
hace 6 años
hace 6 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años